Comparative Laboratory Study: Phytoremediation Ability for Lead, Cadmium, and Copper Using Three Aquatic Plants from the Tigris River in Baghdad City/Iraq - ZR Taha (Journal of Global Pharma Technology, 2018)
The present study was investigate carried out to investigate the possible use of three aquatic plants Hydrilla SP, Vallisneria sp. and Polygonum sp A group of the Tigris River within the Baghdad area to remediate polluted water with lead, cadmium, and copper. after exposure to the concentration (10, 20, 30) ppm of Pb, Cd and, Cu Both individually and for 10 days laboratory, the percentage accumulation of these elements within the plant tissue has been measured as the results showed high efficiency of the Polygonum sp. in Pb accumulation of 55.3, 58, 171.5% in the three respectively and copper accumulation by (52, 65.8, 60.2) % for the concentration (10, 20, 30) Compared to other plants, while the Hydrilla SP exceeds. In the cadmium accumulation of the three concentration (28, 31.1, 40.2)% respectively compared to other plants, as the results prove to be a factor, Pb Cd and cu in the samples of the water from the Tigris River during 2017 within the study area have exceeded the limits allowed by the World Health Organization, Therefore, Hydrilla sp, Vallisneria sp, and Polygonum sp, which are naturally spread in the Tigris River, Which can be used in the Phytoremediation of the river's polluted water by heavy elements.Keywords: Polygonum, Vallisneria, Hydrilla, Phytoremediation.